Hubungan Kenaikan Berat Badan Ibu Selama Hamil dengan Berat Badan Bayi Baru Lahir di UPT Puskesmas Muara Tuhup - Sri Mulyatun; Yena Wineini Migang; Trisaba Trisaba (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2023)
During pregnancy, the growth and development of the fetus can be affected by the health of the mother during pregnancy, such as the mother's weight gain that is less during pregnancy will affect the size of the baby's weight at birth. Birth weight is one indicator of the health of a newborn, which is a healthy and full-term baby. The purpose of this study was to determine the relationship between maternal weight gain during pregnancy and newborn body weight at Muara Tuhup Health Center. This type of research is analytic using a cross sectional study design. The population in this study were all mothers who gave birth at Muara Tuhup Community Health Center with a sample size of 157 respondents. In this study, the statistical test used was the Chi Square test. The statistical test results obtained p value 0.000, with p value <0.05, which means that there is a relationship between maternal weight gain during pregnancy with newborn weight at Muara Tuhup Health Center and the OR value is 59.156, meaning that pregnant women who have gained weight according to the recommendation will had 59 times the chance of giving birth to a baby with normal birth weight compared to pregnant women whose weight gain was not in accordance with the recommendations. For the Muara Tuhup Community Health Center, it can improve services to pregnant women by providing recommendations for weight gain for pregnant women as determined from the BMI before pregnant women to reduce the risk of birth of babies with low or overweight babies